Sinodonty, Sundadonty, and the Beringian Standstill model: Issues of timing and migrations into the New World - Scott, G. Richard; Schmitz, Kirk; Heim, Kelly N.; Paul, Kathleen S.; Schomberg, Roman; Pilloud, Marin A. (Quaternary international, 2018)
C.G. Turner II made dental morphological observations on thousands of Eskimo-Aleuts and American Indians and concluded they were derived from ancestral populations in northeast Asia during the last stages of the Pleistocene. He further distinguished two dental patterns in Asia. In East Asia, populations exhibit Sinodonty, a specialized dentition with intensified trait expressions. Southeast Asians exhibit Sundadonty, a more generalized dentition for crown and root traits. Turner argued all New World groups were derived from Sinodonts. Recent work has led some researchers to conclude there is evidence for the Sundadont pattern in Native American populations, an observation in accord with craniometric research that argues for an early migration of a generalized Asian population, followed by an influx of more specialized northeast Asians. A reanalysis of Turner's dataset fails to reveal evidence for a Sundadont component in the settlement of the Americas, but it does provide support for the Beringian Standstill model proposed by geneticists.